Phytotherapy for Diabetes: A Preclinical Study of Ethanol Extract of Winged Bean (Psophocarpus tetragonolobus L.) Leaves in Diabetic Rat (Rattus norvegicus) Models - Mechiavel Moniharapon; Patrcik Indurian Tahapary; Martha Kaihena; La Eddy (Pattimura University, 2025)
The long-term use of synthetic hypoglycemic agents is known to cause adverse side effects and induce drug resistance. Winged bean (Psophocarpus tetragonolobus L.), a traditional medicinal plant from Maluku, contains secondary metabolites such as flavonoids, saponins, and tannins, which are believed to have potential in lowering blood glucose levels. This study aimed to investigate the effect of ethanolic extract of winged bean leaves on blood glucose reduction and β-cell regeneration in the pancreas of white rats (Rattus norvegicus) as a diabetic model. Thirty rats weighing between 150–200 g were divided into five groups: Group I (negative control), Group II (positive control), and Groups III, IV, and V (diabetic rats treated with ethanolic extract of winged bean leaves at doses of 2.52 mg/g BW, 5.04 mg/g BW, and 7.56 mg/g BW, respectively). Streptozotocin (STZ) was administered to Groups II–V to induce diabetes. Rats with blood glucose levels exceeding 200 mg/dL were subsequently treated with the designated doses of the extract in Groups III–V. On the final day, blood glucose levels were measured, and pancreatic organs were harvested for histological analysis. The results demonstrated that the ethanolic extract of winged bean leaves at a dose of 7.56 mg/g BW effectively reduced blood glucose levels in diabetic rats.